Allergic rhinitis in pediatrics: local therapy - A. V. Kudryavtseva; L. D. Ksenzova (Лечащий Врач, 2021)
The article describes the current view of the topical treatment of allergic rhinitis (AR). Today in the world there is an increase in the incidence of AR, its prevalence in different countries of the world ranges from 4% to 32% of the population, in Russia – 10-24%. Most often, the disease debuts in the first half of life. AR is often associated with bronchial asthma, which is detected in 15-38% of patients with AR. Recently, the attention of researchers has been focused on local AR, which is diagnosed in patients with negative skin and serum tests, when AR is confirmed by provocative tests with significant allergens for the patient with the detection specific IgE in the nasal cavity. When conducting local therapy, nasal sprays are used to eliminate allergens and restore the protective role of epithelial barriers, decongestants are prescribed in a short course, and topical antihistamines are used to relieve allergic inflammation. The main drugs for the treatment of moderate to severe AR are topical glucocorticosteroids: mometasone furoate, azelastine, fluticasone furoate, fluticasone propionate, beclomethasone dipropionate and budesonide. A good effect in the treatment of infectious-allergic rhinitis was obtained with saline solutions.